OPPORTUNITIES FOR PREDICTION OF PULMONARY HYPERTENSION DEVELOPMENT IN PATIENTS WITH VIRAL LIVER CIRRHOSIS - M. V. Chistyakova; A. V. Govorin; E. V. Radaeva (Российский кардиологический журнал)
Aim. To investigate on the prevalence, and opportunities for prediction of pulmonary hypertension in patients with liver cirrhosis of viral origin (VLC).Material and methods. The results analyzed, of the investigation of 85 VLC patients. Mean age 40,1 y. o. According to the severity of pulmonary hypertension (PH), the groups were selected: 1st — no PH systolic pressure in pulmonary artery (SPPA) <30 mmHg, n=62; 2d — SPPA 33-39 mmHg, n=23; controls 22 persons. The Doppler-echo was performed, tissue Doppler on “Vivid S5” equipment (USA). Statistics was done with the Statistica 6,0 software.Results. In VLC patients there was enlarged left atrium, parameters of the LV myocardium mass increased, dilated anulus, stem and branches of pulmonary artery, the velocity of transaortal flow decreased, end-systolic volume of LV increased, global longitudinal, segmentary systolic and diastolic ventricular function decreased, comparing to the healthy persons, and changes were more marked in the persons with moderate PH (p<0,001). The correlation found of pulmonary artery pressure and vena porta diameter (r=0,064, p<0,001). Independent predictors formulated, for PH: time of isovolumetric relaxation on fibrous anulus of trucuspid valve (-0,38±0,1, р<0,001), left ventricle myocardial mass (0,53±0,16, р=0,005).Conclusion. In LC of viral etiology PH is unrare complication (38%). With the increase of pressure in pulmonary artery there is remodelling of theLV with its mass increase, and increase of transaortal velocity, enlargement of the left atrium, pulmonary artery, decrease of systolic and disordered diastolic ventricular function. Independent predictors of pulmonary hypertension are increase of the left ventricle myocardial mass, time of isovolumetric relaxation on fibrous anulus of tricuspid valve.